Pengaruh Ekonomi Hijau dan Ekonomi Sirkular terhadap Pengentasan Kemiskinan: Pendekatan Kuantitatif Berbasis Data Panel - Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin (Economic Development Progress, 2026)
This study aims to analyze the effect of green economy and circular economy on poverty alleviation with unemployment rate as an intervening variable. The research employed a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method through SmartPLS software. The data used were panel data from several provinces in Indonesia during the 2019–2024 period. The research variables consisted of green economy as the first independent variable, circular economy as the second independent variable, unemployment rate as the intervening variable, and poverty alleviation as the dependent variable. Data analysis techniques were carried out through outer model testing, inner model testing, and hypothesis testing using bootstrapping. The results showed that the green economy had a positive and significant effect on poverty alleviation and unemployment rate. Circular economy had a significant effect on unemployment rate but did not have a significant direct effect on poverty alleviation. Unemployment rate had a significant effect on poverty alleviation. In addition, unemployment rate was able to significantly mediate the effect of green economy and circular economy on poverty alleviation. The findings indicate that the implementation of green economy and circular economy plays an important role in sustainable economic development through job creation and improvement of community welfare.